Measures of accommodative function in secondary school year 9 and year 13: a 4-year longitudinal study - Mármol-Errasti, Esther; Cárdenas-Rebollo, José Miguel; Rodán, Antonio; Pagán-Fernández, Encarnación; Jara-García, Laura C.; Palomo-Álvarez, Catalina (Graefe's archive for clinical and experimental ophthalmology, 2022)
Purpose To characterize accommodative function in secondary school children in year 9 and year 13 and assess the possible relationship between daily working conditions (number of near work hours and distances) and accommodation variables related to accommodative excess. Methods This was a prospective study. Participants were 43 subjects who were first examined in year 9 and then again when they were in year 13. The accommodation variables measured in each session were as follows: accommodation amplitude (AA), accommodative response (AR), monocular and binocular accommodation flexibility (MAF and BAF), negative relative accommodation (NRA), and positive relative accommodation (PRA). Other data recorded were the number of hours spent working at near vision tasks and the distances used for these tasks. Participants were classified as those with accommodation variables within the normal range (NA) and those with variables suggesting accommodative excess (AE). Results Several accommodative function variables were below normative values in both year 9 and year 13. The number of subjects classified as having AE went from 27.9% in year 9 to 58.1% in year 13 according to AR ( p < 0.005) and from 23.3 to 46.5% according to MAF ( p = 0.024). More near work was reported in year 13 (44.6 h/week) than year 9 (32.7 h/week) ( p < 0.001). It emerged that subjects in year 13 spent more hours working at near if they had AE than if they were assigned to the NA group. No differences were detected in near work distances used by subjects in the NA and AE groups in both years. Conclusions In both school years, values outside the norm were detected in several accommodative function measures. Also, devoting more hours to near work was linked to a greater extent of accommodative excess. We would therefore recommend regular accommodative function assessment in secondary school children.